2018
DOI: 10.5578/tt.66524
|View full text |Cite
|
Sign up to set email alerts
|

Smoking attitudes of the patients with allergic rhinitis: a comparison with asthma and chronic obstructive pulmonary disease. Are there differences when only upper airways are involved?

Abstract: SuMMArYSmoking attitudes of the patients with allergic rhinitis: a comparison with asthma and chronic obstructive pulmonary disease. Are there differences when only upper airways are involved? Introduction: Despite the well documented relationship between lower airway diseases and smoking, there are limited data about smoking and allergic rhinitis (AR). In this study, we aimed to document the smoking behaviour and environmental tobacco smoke (ETS) exposure of the patients with AR in comparison with patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Data from 68 low- and middle-income countries showed that the overall prevalence of PS in young adolescents aged 12–15 years was 55.9%, ranging from 16.4% in Tajikistan to 85.4% in Indonesia ( 48 ). Despite the relationship between lower airway diseases and PS being documented, there were limited data elucidating the relationship between PS and AR risk ( 49 ), and the conclusion was controversial. A study from the United States reported that after multivariate adjustment, an increased incidence rate of self-reported rhinitis was observed in children and adolescents ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from 68 low- and middle-income countries showed that the overall prevalence of PS in young adolescents aged 12–15 years was 55.9%, ranging from 16.4% in Tajikistan to 85.4% in Indonesia ( 48 ). Despite the relationship between lower airway diseases and PS being documented, there were limited data elucidating the relationship between PS and AR risk ( 49 ), and the conclusion was controversial. A study from the United States reported that after multivariate adjustment, an increased incidence rate of self-reported rhinitis was observed in children and adolescents ( 50 ).…”
Section: Discussionmentioning
confidence: 99%